Brokeback Mountain [videorecording (DVD)] - Lee, Ang, 1954-; Ledger, Heath, 1979-2008; Gyllenhaal, Jake, 1980-; Quaid, Randy, 1950-; Hathaway, Anne, 1982-; Proulx, Annie (Focus Features : Distributed by Universal Studios Home Entertainment, 2006)
It's 1963, a time in the United States when life was simple, straightforward and the lines between the sexes and sex roles were crisply drawn and severely delineated. Ennis Del Mar and Jack Twist find themselves thrown together when they are hired to tend sheep in the remote area of Brokeback Mountain, Wyoming. Because of the job, the two are forced to spend many hours together alone in the wild. Ennis and Jack are inexorably drawn to each other through their proximity, loneliness and through a shared lack of tenderness and emotion in their lives and are emotionally, physically and psychically bonded to each other almost from the start.